Relationship between plasma VEGF level and left ventricular diastolic function in type 2 diabetic renal failure patients - HUANG Yu-jing; WU Jin-quan; HUANG Jia-li (Linchuang shenzangbing zazhi)
Objective To investigate the relationship between plasma VEGF level and left ventricular diastolic function in type 2 diabetic renal failurepatients. Methods Totally 122 cases of patients with type 2 DN renal failure were selected. In addition, 30 cases of healthy volunteers were taken as the control group. According to glomerular filtration rate(eGFR), the patients were divided into the CKD stage 3 group(CKD3 group, n=38), CKD stage 4 group(CKD4 group, n=47) and CKD stage 5 group(CKD5 group, n=37). On the basis of diagnostic criteria of left ventricular diastolic function(LVDD), patients were divided into the LVDD group and non-LVDD group. The levels of plasma VEGF level in each group were analyzed. Meanwhile, the left ventricular posterior wall thickness(LVPWT)、end-diastolic ventricular septal thickness(IVST)、left ventricular end-diastolic volume(LVEDV)、left ventricular ejection fraction(EF)、 left ventricular end-diastolic dimension(LVEDD) and the early diastolic blood flow velocity E peak/diastolic late A peak(E/A) were measured. Then, we analyzed the correlation between plasma VEGF levels and left ventricular diastolic function. Results Compared with the control group, the levels of plasma VEGF of patients with various DN stages were all increased(P<0.05).With the aggravation of renal failure, the levels of VEGF in patients with CKD stage 3, CKD stage 4 and CKD stage 5 gradually increased. Plasma VEGF level in the LVDD group was higher than that in the non-LVDD group(P<0.05). Compared with the normal control group, LVEDV levels in LVDD and non-LVDD patients decreased, and IVST and LVPWT levels increased, with statistically significant differences(P<0.05). Compared with non-LVDD patients, LVEDV and E/A levels in LVDD patients were decreased, while IVST and LVPWT levels were increased, andthe differences were statistically significant. The plasma VEGF level hadpositive correlation with LVPWT、IVST and LVEDD in patients with type 2 DN renal failure(all P<0.05). The level of plasma VEGF level showed positive correlation with LVPWT, IVST and LVEDD of patients with LVDD group(all P<0.05). Conclusions Elevated levels of plasma VEGF in type 2 diabetic renal failure patients had a close relationship with left ventricular diastolic function, which may play a key role in the occurrence and progression of cardiovascular events, and early detection of plasma VEGF level is beneficial to reduce the incidence of cardiovascular complications.